PELATIHAN PADUAN SUARA DAN DIRIGEN: PROFESSIONALISME BERORGANISASI MELALUI SENI SUARA : Indonesia - Fajarina, Maskhurin; Agustina, Ria Kamilah; Rahmawati, Novia Dwi; Laili, Elisa Nurul; Azizah, Ninik; Daristin, Pipit Ertika; Muflihah, Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Community Service plays a strategic role in enhancing human resources through arts and cultural activities that support organizational professionalism. This PKM program on choir and conducting was implemented in the Fatayat NU LKK Pare branch, aiming to improve musical and leadership skills among women cadres. The objectives were: (1) to develop a trained cadre of female choir and conductor members capable of supporting organizational and religious events; (2) to strengthen vocational skills in the field of music and culture through structured and applicable training; and (3) to establish a sustainable system of artistic-musical cadre development. The program involved 120 participants through a two-day intensive workshop and one-month online mentoring. The results demonstrated significant improvements in vocal quality, conducting skills, teamwork, and organizational professionalism. Moreover, the program fostered women empowerment and cultural preservation in local communities. This study concludes that choir and conductor training not only enhances artistic competence but also promotes leadership, teamwork, and organizational sustainability within religious-based women organizations.